Multiparametric Analysis of Sniff Nasal Inspiratory Pressure Test in Middle Stage Amyotrophic Lateral Sclerosis - Sarmento, Antonio; Aliverti, Andrea; Marques, Layana; Pennati, Francesca; Dourado-Júnior, Mario Emílio; Fregonezi, Guilherme; Resqueti, Vanessa (Frontiers in Neurology, 2018)
The relaxation rates and contractile properties of inspiratory muscles are altered with inspiratory muscle weakness and fatigue. This fact plays an important role in neuromuscular disorders patients and had never been extensively studied in amyotrophic lateral sclerosis (ALS). In this cross-sectional study, these parameters were investigated non-invasively through nasal inspiratory sniff pressure test (SNIP) in 39 middle stage spinal onset ALS subjects and compared with 39 healthy controls. ALS patients were also divided into three subgroups according to a decline in their percentage of predicted forced vital capacity (FVC%pred) as well as a decline in the ALS functional rating scale score and its respiratory subscore (R-subscore) in order to determine the best parameter linked to early respiratory muscle weakness. When compared with healthy subjects, middle stage ALS subjects exhibited a significantly lower (p < 0.0001) maximum relaxation rate and maximum rate of pressure development (MRPD), as well as a significantly higher (p < 0.0001) tau (τ), contraction time, and half-relaxation time. The results from receiver operating characteristic curves showed that MRPD (AUC 0.735, p < 0.001) and FVC%pred (AUC 0.749, p = 0.009) were the best discriminator parameters between ALS patients with ≤30 and >30 points in the ALS functional rating scale. In addition, 1/2RT (AUC 0.720, p = 0.01), FVC%pred (AUC 0.700, p = 0.03), τ (AUC 0.824, p < 0.0001), and MRPD (AUC 0.721, p = 0.01) were the parameters more sensitive in detecting a fall of three points in the R-subscore. On the other hand, MRPD (AUC 0.781, p < 0.001), τ (AUC 0.794, p = 0.0001), and percentage of predicted of SNIP (AUC 0.769, p = 0.002) were the parameters able to detect a fall in 30% of the FVC%pred in middle stage ALS patients. The contractile properties and relaxation rates of the diaphragm are altered in middle stage spinal onset ALS when compared with healthy subjects. These parameters are able to discriminate between those middle stage ALS subjects with early decline in inspiratory muscle function and those who not.